2011
DOI: 10.1007/s00464-010-1541-9
|View full text |Cite
|
Sign up to set email alerts
|

Needle oophoropexy: a new simple technique for ovarian transposition prior to pelvic irradiation

Abstract: Percutaneous needle transposition of the ovaries is a simple, effective, reliable, and easy-to-perform technique. It has short learning curve and can be done by less experienced laparoscopic surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 24 publications
0
30
0
1
Order By: Relevance
“…In a review of 44 cases, Bisharah and Tulandi [41] reported that laparoscopic ovarian transposition in women younger than 40 years is associated with preservation of ovarian function in 88.6% of cases, similar to the rate of 83% for ovarian transposition by laparotomy reported by Husseinzadeh et al [42]. However, laparotomy is associated with a large abdominal incision, a long hospital stay, and an increased risk of adhesions formation and intestinal obstruction or ileus [41,43]. More importantly, laparotomy requires a delay of several months to allow the incision to heal before radiation, during which time the ovaries can migrate back to their original position, thereby explaining many cases of ovarian failure [36].…”
Section: Embryo Cryopreservationmentioning
confidence: 76%
“…In a review of 44 cases, Bisharah and Tulandi [41] reported that laparoscopic ovarian transposition in women younger than 40 years is associated with preservation of ovarian function in 88.6% of cases, similar to the rate of 83% for ovarian transposition by laparotomy reported by Husseinzadeh et al [42]. However, laparotomy is associated with a large abdominal incision, a long hospital stay, and an increased risk of adhesions formation and intestinal obstruction or ileus [41,43]. More importantly, laparotomy requires a delay of several months to allow the incision to heal before radiation, during which time the ovaries can migrate back to their original position, thereby explaining many cases of ovarian failure [36].…”
Section: Embryo Cryopreservationmentioning
confidence: 76%
“…In 2011, Gareer and associates described a modified multiport lateral oophoropexy that employed percutaneous passage of a straight needle [18]. Two years later Lacher et al produced the first publication outlining an experience utilizing SIPES in the management of ovarian pathology [19].…”
Section: Discussionmentioning
confidence: 99%
“…Il est à noter que l'objectif premier de la transposition ovarienne est la préservation de la fonction ovarienne endocrinienne, et que le maintien de la fertilité implique également l'épargne de l'utérus lors de la radiothérapie. Le tableau I résume les expériences cliniques rapportées dans la littérature [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Transposition D'ovairesunclassified